2007
DOI: 10.1007/s10439-007-9365-z
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Prospective Registration of High-Resolution Trabecular Bone Images of the Tibia

Abstract: Magnetic Resonance Imaging (MRI) longitudinal studies conducted to assess changes in tibia bone quality impose strict requirements on the reproducibility of the prescribed region acquired. Registration, the process of aligning two images, is commonly performed on the images after acquisition. However, techniques to improve image registration precision by adjusting scanning parameters prospectively, prior to image acquisition, would be preferred. We have adapted an automatic prospective mutual information based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…2,3,19 Three-dimensional registration is already used in a novel peripheral forearm QCT scanner with a spatial resolution of about 150 lm 14 for human in vivo investigations. However, in this study we did not register serial lCT images but concentrated on multimodality registration of lCT and lMR images of excised bones which can be used, for example, to better quantify damage caused by osteoarthritis in cartilage and corresponding subchondral bone structure 1 or to correlate local inflammatory processes with deterioration of bone tissue.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,19 Three-dimensional registration is already used in a novel peripheral forearm QCT scanner with a spatial resolution of about 150 lm 14 for human in vivo investigations. However, in this study we did not register serial lCT images but concentrated on multimodality registration of lCT and lMR images of excised bones which can be used, for example, to better quantify damage caused by osteoarthritis in cartilage and corresponding subchondral bone structure 1 or to correlate local inflammatory processes with deterioration of bone tissue.…”
Section: Introductionmentioning
confidence: 99%
“…During the preparation of this article an article appeared on 3D prospective registration of trabecular bone images of the tibia (23). In that work a localizer-based scheme was used to achieve prospective registration by maximizing mutual information between baseline and follow-up images.…”
Section: Discussionmentioning
confidence: 99%
“…A technique based on 2D localizer images of the brain aligned with the three principal axes of the scanner has been used to achieve submillimeter and subdegree repositioning accuracy in about 5 min (22). Recently, a mutual information maximization metric optimized for MR spectroscopic imaging of the brain has been demonstrated to yield accurate results in musculoskeletal imaging (23).…”
mentioning
confidence: 99%
“…Coregistration of pMRI was manually guided by anatomical features and matched slice-by-slice while only orthogonal transformations were applied. However, Blumenfeld et al (26) demonstrated that trabecular bone structural measures calculated from automatic vs manual registration methods did not differ significantly, and test-retest precision error for both methods remained well within 5%.…”
Section: Study Limitationsmentioning
confidence: 98%